A world appears : a journey into consciousness - Pollan, Michael (Penguin Press, 2026)
"When it comes to the phenomenon that is consciousness, there is one point on which scientists, philosophers, and artists all agree: that it feels like something to be us. Yet the fact we have subjective experience of the world remains one of nature's greatest mysteries. How is it that our mental operations are accompanied by feelings, thoughts, and a sense of self? What would a scientific investigation of our inner life look like, considering we have as little distance and perspective on it as fish do of the sea? In A World Appears, Michael Pollan traces the unmapped continent that is consciousness, bringing radically different perspectives-scientific, philosophical, literary, spiritual and psychedelic-to see what each can teach us about this central fact of life. When neuroscientists began studying consciousness in the early 1990s, they sought to explain how and why three pounds of spongy grey matter could generate a subjective point of view-assuming that the brain is the source of our felt reality. Pollan takes us to the cutting edge of the field, where scientists are entertaining more radical (and less materialist) theories of consciousness. He introduces us to "plant neurobiologists" searching for the first flicker of consciousness in plants; scientists striving to engineer feelings into AI, and psychologists and novelists seeking to capture the felt experience of our slippery stream of consciousness. In Pollan's dazzling exploration of consciousness, he discovers a world far deeper and stranger than our everyday reality. Eye-opening and mind-expanding, A World Appears takes us into the laboratories of our own minds, ultimately showing us how we might make better use of the gift of awareness to more meaningfully connect with our deepest selves"-- Provided by publisher.